Making Pond And Feed Of Catfish By Farmer’s Wife At Nagari Limau Gadang - Armen Amir; Mades Fifendy; Ristiono Ristiono (UNIVERSITAS NEGERI PADANG, 2017)
The life of Nagari Limau Gadang residents is poor. They conduct economic activities in Kerinci Seblat National Park (TNKS), so that TNKS become damaged. To reduce the economic activities of the people in TNKS, it is necessary to conduct economic activities outside TNKS to improve the family economy. Catfish farming can serve as the main effort to increase family income. Economically catfish farming is very profitable. Catfish farming is not difficult and can be done by farmers who do not usually cultivate freshwater fish. The right family member is empowered to improve the family economy through the cultivation of catfish is the farmer's wife. Farmer’s wives in Limau Gadang Nagari tend not to improve the family economy, they play the role of taking care of children, doing housework and sometimes delivering food to the fields and to the fields. The farmer’s wife activity is only fulfilling the wife's obligation to husband in married life. Farmers' wives are economically unproductive in improving the family economy. The goal to be achieved in this research is for the wife of farmers can contribute to improve the family economy. Specific targets to be achieved in this study is the wife of skilled farmers cultivate catfish, Nagari Limau Gadang population increases their living standards and TNKS in Nagari Limau Gadang free from the pressure of the population. How to research, selected 20 poor farmer's wife then trained to make ponds and pellets. The pools made are the main pond, spawning pond, nursery pool and pond enlargement. Pellet made from raw trash fish, quail feces, fine bran and cassava. The pellet formulation is made of 4 kinds. Each formulation produces a quality pellet. Based on laboratory test produced pellet contains very good nutrition for enlargement catfish. The nutritional range of protein is 21,79%-34,60%, fat is 1,95%-2,32% and carbohydrate is 26,55%-39,65%. The farmer's wife understands and skillfully creates ponds and pellets. Pellet made from raw materials trash fish, quail feces, fine bran and cassava can be used as raw material pellet. Keyword: cultivation, catfish, farmer's wife, income, family.